How did Teacher Collaboration Develop During the Pandemic? A Case Study of six Public High Schools in Santiago, Chile - Weinstein, Jose (2023)
Background. Although it is often assumed that the COVID-19 crisis led to increased teacher collaboration, there is a scarcity of empirical studies in this area. Aims. This research aims to investigate the impact of the pandemic on teacher collaboration in six public high schools in the Metropolitan Region of Chile over a two-year period (2020-2021). Methods. A qualitative methodology was employed, utilizing a multiple case study design, with a focus on conducting individual semi-structured interviews. Principals and teachers from the six high schools were interviewed three times, resulting in a total of 146 interviews. Results. I) The crisis resulted in three distinct moments: emergency responses, remote working, and adapted face-to-face modes that affected collaborative work. II) Three shared tasks emerged: remote teaching, addressing emerging student needs (prioritizing learning), and renewing teaching approaches on which teachers focused their professional collaboration. III) Two key factors, namely social capital and a pre-existing culture of collaboration, as well as effective school leadership, played a mediating role in the varied responses observed among the high schools. Conclusions. Although the crisis initially contributed to increased teacher collaboration across all the high schools examined, this collaboration often diminished as the school year progressed and returned to a more normal state, without extending over time. Only a few high schools were able to sustain the progress made and implement changes in their institutional and pedagogical management, as well as in their teaching working conditions. These changes facilitated a successful transition to face-to-face teaching. The key factor to understand the difference between the high schools lay in organizational learning, which can be defined as the schools’ capacity to convert crises into opportunities for transformation, specifically through collaboration among teachers.